2010
DOI: 10.1111/j.1365-246x.2010.04885.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced anisotropy in brine saturated shale

Abstract: S U M M A R YThis paper reports the intrinsic and crack-induced anisotropic properties of a set of preserved, brine-saturated shale samples and their response to external stresses. We used undrained multistage triaxial tests to evaluate how the ultrasonic wave velocities and their anisotropy changed with increasing isotropic and differential stress conditions. In addition, the impact of stress orientation with respect to fabric orientation was evaluated. An array of ultrasonic transducers allowed to measure fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The suggested method works quite well for predicting anisotropic elastic moduli of shales on the basis of CPD and silt fraction. However, it fails to predict stress dependency of elastic properties of shales (Pervukhina et al, 2008a(Pervukhina et al, , 2008b, which has been observed in many experiments (e.g., Jakobsen and Johansen, 2000;Dewhurst and Siggins, 2006;Delle Piane et al, 2010;Kuila et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…The suggested method works quite well for predicting anisotropic elastic moduli of shales on the basis of CPD and silt fraction. However, it fails to predict stress dependency of elastic properties of shales (Pervukhina et al, 2008a(Pervukhina et al, , 2008b, which has been observed in many experiments (e.g., Jakobsen and Johansen, 2000;Dewhurst and Siggins, 2006;Delle Piane et al, 2010;Kuila et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…5 Ultrasonic measurements under variable saturation and pressure conditions in the laboratory have revealed that anisotropy of elastic wave propagation is caused mainly by the preferential alignment of mineral grains and thin layers. 6,7 Near cracks, the effective density and thickness are clearly different from those at other locations. Such heterogeneity is minimized at high confining pressures upon the closure of cracks.…”
Section: Resultsmentioning
confidence: 89%
“…Ultrasonic systems have been widely used to study shale anisotropy in the laboratory. 6,7 These studies have mainly focused on the elastic properties of shales, and have revealed that the preferential alignment of clay minerals and cracks is the major factor leading to the intrinsic anisotropy of shales.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative analysis was performed on the XRD data using the commercial package SIROQUANT (Sietronics Pty Ltd). Further details of the XRD method can be found elsewhere [36]. For XRD analysis bulk samples were pre-ground for 15 s in a tungsten carbide mechanical mill to pass through a 0.5 mm sieve.…”
Section: X-ray Diffraction (Xrd) Studymentioning
confidence: 99%